The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3389/fenvs.2019.00013
|View full text |Cite
|
Sign up to set email alerts
|

Using the DSSAT Model to Support Decision Making Regarding Fertilizer Microdosing for Maize Production in the Sub-humid Region of Benin

Abstract: 2 could be achieved in almost 100% of the years. Furthermore, combined application consistently reduced the inter-annual yield variability. Considering this as well as the other benefits of manure for soil health, combining microdosing with small quantities of manure would be recommended to increase the sustainability of the system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 51 publications
1
20
0
Order By: Relevance
“…Their recommendations that higher yields will be obtained under intensification are in line with [29], who warn about the production risks associated with non-adopters of crop management strategies. However, since intensification is yet to be achieved, despite being effective, mostly due to limited income for many farmers in the SSA, there is an ongoing shift toward advocating MD [21,22,30,[43][44][45]. The findings of this study ( Figure 3) provide a unique understanding of the sustainability, and the associated limitations, of MD for pearl millet farmers.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Their recommendations that higher yields will be obtained under intensification are in line with [29], who warn about the production risks associated with non-adopters of crop management strategies. However, since intensification is yet to be achieved, despite being effective, mostly due to limited income for many farmers in the SSA, there is an ongoing shift toward advocating MD [21,22,30,[43][44][45]. The findings of this study ( Figure 3) provide a unique understanding of the sustainability, and the associated limitations, of MD for pearl millet farmers.…”
Section: Discussionmentioning
confidence: 97%
“…Long-term experiments are best for the evaluation of feasible cropping strategies; however, such information is rarely available for crops in SSA, as experiments are typically conducted for two to three seasons. Consequently, combining results from short-term experiments with validated crop models is a less costly, yet reliable, method for deriving sustainable cropping strategy recommendations [43]. In this study, the DSSAT CERES Millet model is calibrated and evaluated for different crop parameters (anthesis days, maturity days, as well as tops weight and grain yield) ( Table 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural systems models have a large potential to assist with assessing microdosing new techniques and risks. For example, a recent study in Benin, West Africa, using DSSAT with the Crop Environment Resource Synthesis (CERES)‐Maize model found that combining manure with microdosing techniques was slightly riskier but returned better yields in the long term (Tovihoudji et al, 2019). This study did not simulate P directly, and further research is needed to investigate crop P requirements to predict the depletion of available P. Other factors such as climatic effects on crop growth, P loss pathways, and additional nutrient requirements should be incorporated to improve temporal predictions of P supply through the model.…”
Section: Research Gap 1: Agricultural Systems Modeling To Improve Phomentioning
confidence: 99%
“…Over the years, the use of the CERES-maize model in making management decisions has been increasing in Africa. For instance, it was used to; evaluate climate-sensitive farm management practices in the Northern Regions of Ghana ( MacCarthy et al, 2017 ); identify appropriate sowing dates and nitrogen rates in Zambia ( Chisanga et al, 2014 ); simulate nitrogen and phosphorus uptakes and soil moisture dynamics in West Africa ( Amouzou et al, 2018 ); and recently used in Benin Republic to provide support decision making regarding fertilizer micro-dosing for maize production ( Tovihoudji et al, 2019 ). In Nigeria, the model has been used for the determination of the nitrogen fertilization requirements and optimum planting dates of maize ( Adnan et al, 2017a , 2017b ).…”
Section: Introductionmentioning
confidence: 99%